Ecosystem map: a systemic view of Edmonton's transit system - Cox, Lisa (My University, 2022)
Edmonton's Transit System (ETS) is a multi-faceted, rider-driven transportation system, making it an excellent candidate for Design thinking and System Mapping. ETS operates within the larger City of Edmonton System and has complex pain points regarding safety and security both within and outside of their direct control. The top of the map shows the system hierarchy and the interdependent relationship between the ETS System and the Rider Experience. Rider Experience affects riders' willingness to participate in the ETS System (Ridership), affecting the ETS System through funding and budget. The Community Partners, Emergency Services, and ETS Personnel chart within the hierarchy shows the top-level influence of these stakeholders within the greater ETS system. The second portion of the infographic highlights the Riders' Journey, illustrated by a Journey Map divided into each phase of ETS's System. Riders navigate various obstacles: Phase 1: Stop Experience, Phase 2 Station Experience, and Phase 3 - Onboard Experience. The final portion of the infographic is the inventory of touchpoints defined by phase within the ETS system. Touchpoints are categorized by interaction type: Information, Actors/Stakeholders, Safety Features, and Security Risks. Each touchpoint type is indicated through iconography, defining the different characteristics of that interaction. Finally, the User/Rider loops back into the top-level, outlining the interconnected nature of the System. Analysis of the ETS Ecosystem through a Design Thinking Lens and User-Centered approach enables a deeper understanding of the ETS System as a whole and how to best proceed when designing future solutions. Bachelor of Design, DESN 445.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta.
Keywords: design thinking; infographics